IMPLEMENTASI WALK IN CUSTOMER (WIC) DAN ENHANCED DUE DILIGENCE KEPADA NASABAH SEBAGAI PENCEGAHAN MONEY LAUNDERING PT. BANK SUMUT KCP SYARIAH H.M YAMIN - Mufidatul Himmah; Mohammad Alief Hidayatullah; Siti Fatimah (JURNAL PROFIT, 2022)
Banking institutions are institutions that are often used by the public to carry out financial transactions, whether in the form of savings, transfers, investments and others. In this case, Islamic Banking carries out funding and lending activities by promoting various types of financial transaction services, becoming the main center in crime. money laundering and terrorism financing to hide illegal money. Therefore, the OJK has made regulations regarding the prevention of Money Laundering and the financing of Terrorism which includes CDD and EDD PT. Bank Sumut Syariah KCP H.M Yamin has implemented Customer Due Diligence on Walk In Customer (WIC) and Enhanced Due Diligence on Customers as an effort to prevent money laundering and terrorism financing. In this journal research using qualitative methods with a descriptive approach. the data taken is by interview and observation techniques. Observations indicate that the implementation of WIC on Customer Due Diligence is carried out when the Bank doubts customer information by conducting identification and verification. In addition, at WIC where previously WIC did not need to report to Customer Service when making transactions and went directly to the teller. However, for now there has been a circular letter of change from the Head Office of Bank Sumut Syariah regarding the implementation of WIC where WIC is required to report to Customer service first after obtaining approval from CS, then WIC can go directly to the teller. The implementation of Enhanced Due Diligence is carried out for Politically Exposed Person customers. But in practice at PT. Bank Sumut Syariah KCP H.M Yamin is carried out if there are suspicious transactions or when there are cases.